Clayey soil stabilization using flyash and jute fibre. (2022) - Gupta, Adarsh; Kumar, Mukesh
Highlights: Soil is only materials which is easily available on the earth and used in many purposes in construction of structure. Soil stabilization varies a great deal and improves the bearing capacity and maintenance. Increased higher resistance values, reduced plasticity, lower permeability, reduced pavement thickness, elimination of excavation, and importing new materials are all advantages of soil stabilization. Abstract: Soil is only materials which is easily available on the earth and used in many purposes in construction of structure. Soil stabilization varies a great deal and improves the bearing capacity and maintenance. Increased higher resistance values, reduced plasticity, lower permeability, reduced pavement thickness, elimination of excavation, and importing new materials are all advantages of soil stabilization. The Present study has been carried out for stabilization of locally available clayey soil with varying percentages of Fly ash and Jute Fibers. The Characterization of materials is being followed with the sample preparation and mechanical testing such as Standard Proctor Test, Un-confined Compression Testing and California Bearing Ration Test. The Modied Samples have showcase a considerable improvement in the engineering properties of soil. There after conclusion, Practical applications and Future Scope of study concludes the outcomes and suggestion from the study.